Assessing the Functional and Structural Properties of Peanut Meals Modified by Transglutaminase-Coupled Glycation - Yan Liu; Tingwei Zhu; Fusheng Chen; Xingfeng Guo; Chenxian Yang; Yu Chen; Lifen Zhang (Foods)
To increase the added value of peanut meal (PM, protein content of 46.17%) and expand its application in food processing, cold-pressed PM was modified via transglutaminase (TGase)-coupled glycation to enhance its functional properties. The effects of the modification conditions (i.e., PM concentration, PM/glucose mass ratio, temperature, and time) on the functional properties of PM were investigated, and its structural properties were evaluated using water contact angle measurements, fluorescence spectroscopy, and Fourier-transform infrared spectroscopy. It was found that TGase-coupled glycation modification altered the secondary structure of PM and increased both the water contact angle and the surface hydrophobicity, thereby significantly affecting its functional properties. Additionally, superior emulsification, foaming, and oil-absorbing properties were achieved for the modified PM, which were named EPM, FPM, and OPM, respectively (specimens under different modification conditions). Notably, the emulsification activity of the EPM sample was enhanced by 69.8% (i.e., from 18.48 to 31.38 m2/g); the foaming capacity of the FPM specimen was increased by 84.00% (i.e., from 21.00 to 46.00%); and the oil-absorbing capacity of the OPM sample was enhanced by 359.57% (i.e., from 1.41 to 6.48 g/g protein).